Penerapan Program Kampus Mengajar terhadap Peningkatan Kemampuan Literasi Siswa di SDN 134 Kota Jambi: Implementation of the The Campus Teaching Program towards Improving Students' Literacy Abilities At SDN 134 Jambi - Frisha Salsabillah; Eddy Pahar Harahap; Sophia Rahmawati (Universitas Tidar, 2026)
The Campus Teaching Program (Kampus Mengajar/MBKM) is an innovative initiative from the Ministry of Education that provides opportunities for university students to engage directly in solving educational problems in schools. This research analyzes the impact of the program on improving students' literacy abilities at SD Negeri 134 Kota Jambi through a qualitative descriptive approach with data triangulation (N=45 students). The research results demonstrate: (1) significant improvement in students' perception of literacy by 24 percentage points (64% → 88%), (2) interaction-based learning strategies showing the highest implementation frequency (88-94%), (3) major challenges related to resources, time management, student ability variation, and parental engagement, and (4) success-supporting factors including effective collaboration, student commitment, and institutional support. In conclusion, the Campus Teaching Program effectively improves literacy through integration of modern learning theory elements, but requires attention to social and economic contextual factors for more sustainable impact